Analysis of Sensors as Components of Mobile Robots - Kuzmenko, Oleksandr; Чумак, В. С.; Шевцов, І. О.; Бойко, Н. В. (MC&FPGA, 2022)
Given the current trends in robotics, the paper provides an overview of sensors for use in robotics. It is given what characteristics the sensors must meet for further integration into mobile works.
Keywords: robot; sensor; device; characteristics of sensors; types of sensors